León Llerena, Laura. Reading the Illegible: Indigenous Writing and the Limits of Colonial Hegemony in the Andes. Tucson: University of Arizona Press, 2023, 264 pp. - Dedenbach-Salazar Sáenz, Sabine (2023)
No presenta resumen.